ChemInform Abstract: 3‐Pyrrolyl‐Oxindoles as Efficient Nucleophiles for Organocatalytic Asymmetric Synthesis of Structurally Diverse 3, 3′‐Disubstituted Oxindole Derivatives. Issue 23 (June 2015) - Cui, Bao‐Dong; You, Yong; Zhao, Jian‐Qiang; Zuo, Jian; Wu, Zhi‐Jun; Xu, Xiao‐Ying; Zhang, Xiao‐Mei; Yuan, Wei‐Cheng
Abstract A squaramide‐substituted cinchona alkaloid is successfully applied as catalyst for the synthesis of chiral oxindoles such as (III) and (V) by Michael addition of 3‐pyrrolyloxindoles with nitroalkenes.